ANALYSIS OF THE MECHANICAL AND PHYSICAL PROPERTIES OF ADOBE COMPACTED WITH ICHU AND WITH PINE FIBERS (LACCEI, 2024)
This research was carried out with the objective of determining the mechanical and physical properties of compacted adobe by incorporating plant materials in its preparation. For which, 2.5% ichu fiber was used as a standard sample in comparisons to the use of three levels of pine fiber (2.5%, 5% and 7%). The compression, bending and absorption properties were analyzed for which 24 adobes were made for each of the indicated addition percentages Obtaining, as an answer that the adobe with ichu fiber has better compression resistance 42.75 kg/cm², compared to 35.65 kg/cm², 34.68 kg/cm² and 28.95 kg/cm², for the levels 2.5%, 5% and 7% of pine fiber. When evaluating the resistance to flection, the adobes made at 2.5% with ichu fiber reached a resistance of 33.02 kg/cm², being greater than the resistance of: 27.07 kg/cm², 25.20 kg/cm² and 26.00 kg/cm² for 2.5 %, 5% and 7% pine fiber Likewise, when evaluating the absorption of water, it was obtained as results that the adobe with Ichu fiber was 2.92% compared to 2.74%, 3.05% and 2.80% for 2.5%, 5% and 7% of pine fiber respectively. It is concluded: That the addition of 2.5% ichu fiber generates greater resistance to compression and flection, compared to the addition of pine fiber in 2.5%, 5% and 7%, but has lower absorption compared to pine fiber.